Synthesis of Cuboctahedral CeO2 Nanoclusters and Their Assembly into Cuboid Nanoparticles by Oriented Attachment. Issue 4 (23rd February 2017) - Maya‐Johnson, Santiago; Gracia, Lourdes; Longo, Elson; Andres, Juan; Leite, Edson R.
Abstract: Here, we describe a simple approach to control the oriented attachment process through selective ligand scavenging from the 100 facets of CeO2 nanoclusters. Aggregates of these nanoclusters smaller than 10 nm with controlled shapes and exposed facets were obtained. For the synthesis of the cuboctahedral CeO2 nanoclusters, we developed a solvent‐controlled synthesis approach based on a non‐hydrolytic sol–gel process and used an ester aminolysis reaction to control ligand scavenging from the 100 facets. First‐principle calculations allowed us to understand and interpret, at the atomic level, the effects of shape control on the synthesis. Fine‐tuning of the desired morphologies can be achieved by controlling the values of the surface energies, which leads to the formation of morphologies that the classic growth process does not allow. Abstract : Non‐classical growth process : By using selective removal of a ligand a very high control over the oriented attachment process is achieved, which allows control over the assembly of CeO2 nanoclusters.